MitoTEMPOL Inhibits ROS-Induced Retinal Vascularization Pattern by Modulating Autophagy and Apoptosis in Rat-Injected Streptozotocin Model - Rova Virgana; Nur Atik; Julia Windi Gunadi; Evelyn Jonathan; Dona Erisa Ramadhani; Ray Sebastian Soetadji; Hanna Goenawan; Ronny Lesmana; Arief Kartasasmita (Life, 2022)
Diabetic retinopathy leads to retinal malfunction, blindness, and reduced quality of life in adult diabetes patients. The involvement of reactive oxygen species (ROS) regulation stimulated by high blood glucose levels opens the opportunity for ROS modulator agents such as MitoTEMPOL. This study aims to explore the effect of MitoTEMPOL on ROS balance that may be correlated with retinal vascularization pattern, autophagy, and apoptosis in a streptozotocin-induced rat model. Four groups of male Wistar rats (i.e., control, TEMPOL (100 mg/kg body weight [BW]), diabetic (streptozotocin, 50 mg/kg BW single dose), and diabetic + TEMPOL; n = 5 for each group) were used in the study. MitoTEMPOL was given for 5 weeks, followed by funduscopy, and gene and protein expression were explored from the rat’s retina. Streptozotocin injection decreased bodyweight and increased food and water intake, as well as fasting blood glucose. The results showed that MitoTEMPOL reduced retinal vascularization pattern and decreased superoxide dismutase gene expression and protein carbonyl, caspase 3, and caspase 9 protein levels. A modulation of autophagy in diabetes that was reversed in the diabetic + TEMPOL group was found. In conclusion, MitoTEMPOL modulation on autophagy and apoptosis contributes to its role as a potent antioxidant to prevent diabetic retinopathy by inhibiting ROS-induced retinal vascularization patterns.